First report of the family Laubierinidae Warén & Bouchet, 1990 (Gastropoda: Tonnoidea) in the southwestern Atlantic - Pastorino, Roberto Santiago Guido (2016)
The presence of Laubierina peregrinator Warén & Bouchet, 1990 (Tonnoidea: Laubierinidae) isreported for the first time in the continental slope of Argentina at a depth of 2934 m. Thisconstitutes the first mention of the species in the literature other than the originaldescription. Minor differences of shell and radula are compared with the original description.This record, together with two others from southwestern Africa and Mozambique Channel,suggest that L. peregrinator is a southern hemisphere species.